Evaluation of urticaria patients before and during the period of the COVID-19 pandemic: A retrospective study - Akca, Hanife Merve; Tuncer Kara, Kevser (Wiley, 2021)
The COVID-19 pandemic is the most serious health crisis facing the modern world; hospital admissions have risen dramatically. Urticaria is characterized by itchy edematous papules/plaques, angioedema, and involvement of one or both of the deep dermis or subcutis. We investigated the effect of the COVID-19 pandemic on the incidence of acute and chronic urticaria, the proportions of urticaria patients among all dermatology patients before and after the onset of the pandemic, and age and sex characteristics. About 57 patients diagnosed with urticaria before the onset of the COVID-19 pandemic in December 2019 and January and February 2020 at the Dermatology Polyclinic of Beysehir State Hospital, and 25 patients diagnosed within 3 months (March-May 2020) after the onset of the pandemic, were included. We retrospectively recorded age, sex, and the duration of the disease. Patients were divided into those with acute and chronic urticaria using the EAACI/GA(2)/LEN/EDF/WAO guidelines and data obtained before and after the onset of the pandemic were compared. Fifty-one (62.2%) patients were female and the mean patient age was 40.88 +/- 17.38 years. We found no significant difference in the mean age or sex distribution before and after the onset of the pandemic (P = .341; P = .604). The proportion of urticaria patients (1.6%) among all dermatology patients treated in a 3-month period after the onset of the pandemic was higher than that before the pandemic (1.19%; P < .001). During the pandemic, the acute urticaria rate was significantly higher than before the pandemic (P = .002). The urticaria rate (particularly that of acute disease) increased during the COVID-19 pandemic. Dermatologists should consider whether patients with urticaria might be infected with COVID-19.
Keywords: urticaria; acute urticaria; COVID-19 pandemic